(untitled) (Ta’limning zamonaviy transformatsiyasi, 2024)
ABSTRACT. Learning English as a second language can be challenging, especially can be difficult, particularly when it comes to memorizing new words. Vocabulary is vital for effective communication, comprehension, and fluency. That is why improving vocabulary skills are important for beginners to progress in their language abilities and communication skills. This article looks at creative and effective strategies that teachers can use to help new learners grow their vocabulary and develop a varied language skill.